2008
DOI: 10.1055/s-2007-989423
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heart Rate Variability to Estimate LT and VT

Abstract: The purpose of this study was to determine if changes in heart rate variability during incremental exercise could be used to estimate lactate threshold and ventilatory threshold in healthy adults. Twenty-four adults performed graded maximal cycle ergometry to volitional fatigue. Blood lactate, heart rate, RR interval, and respiratory gas exchange were monitored. Heart rate variability was analyzed using time domain indices (standard deviation and mean successive difference). A marked RR interval deflection poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
181
3
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(208 citation statements)
references
References 31 publications
10
181
3
14
Order By: Relevance
“…An increasing amount of evidence shows that the HRVT point coincides with the ventilatory and lactate threshold 4,11,12,13 , which are considered simple and practical measures for estimating the aerobic/anaerobic transition. Therefore, our results suggest that, beyond being a valid indicator of parasympathetic withdrawal, HRVT is a reproducible measure in a submaximal exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An increasing amount of evidence shows that the HRVT point coincides with the ventilatory and lactate threshold 4,11,12,13 , which are considered simple and practical measures for estimating the aerobic/anaerobic transition. Therefore, our results suggest that, beyond being a valid indicator of parasympathetic withdrawal, HRVT is a reproducible measure in a submaximal exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…Another relative limitation that should be addressed is the absence of ventilatory and/or lactate threshold assessment during the incremental stress test. However, the primary objective of this study was to evaluate the reproducibility of HRVT and r-MSSD analysis immediately after a submaximal stress test and not the validity of these tools, which has been tested in previous work 4,11,13 . Another important observation is the wide variation in BMI in the sample studied, which divides the sample in normal weight and overweight men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…second lactate and ventilatory threshold -LT 2 and VT 2 , respectively) (3,5). As a result, studies have suggested that HRV analysis may be a potential and useful tool to estimate the exercise intensity of the first and second physiological thresholds (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%